Ethnochemical Investigation of Traditional Maize Fermentation Practices in Rural Andean Communities of Peru - Reyna Gladys Cárdenas Vda. de Reategui; Nasim Shekari; Abhinav Dhar (Cahaya Ilmu Cendekia Publisher, 2026)
traditional maize fermentation practices and their underlying chemical processes in Andean communities of Peru using an ethnochemical approach. Methodology: This study employed an integrated ethnographic and chemical analysis approach, including semi-structured interviews, participant observation, and laboratory analyses using GC-MS, HPLC, and spectrophotometry to evaluate physicochemical parameters and compound profiles. Main Findings: Results showed a significant decrease in pH (6.8 to 3.9) and an increase in ethanol content during fermentation (p < 0.05). Ethnographic findings revealed structured local knowledge systems that regulate fermentation processes, which were found to correlate with measurable chemical transformations. Novelty/Originality of this study: This study provides empirical evidence linking cultural fermentation practices with biochemical processes, demonstrating that traditional knowledge systems function as adaptive regulatory mechanisms within fermentation systems.